Simplify the following expression to a single trigonometric term sin(360-x)*tan(-x)/cos(180 x)*(sin^2A cos^2A) answer= -sinx*-tanx/cosx*(1) after that how do i continue?

1 answer

sin(360-x) = -sin(x)
tan(-x) = -tan(x)
cos(180-x) = -cos(x)

so, you have

sin(x)tan(x)/cos(x) = sin^2(x)/cos^2(x) = tan^2(x)

Not sure where the A comes from, but you get the idea. Just reduce everything to simple trig functions and then combine them. If you need further help, please fix all the typos and get back to us.
Similar Questions
  1. Simplify #3:[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
    1. answers icon 1 answer
  2. Trigonometric IdentitiesProve: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
    1. answers icon 0 answers
  3. Which of the following are trigonometric identities?(Can be more then one answer) tanx cosx cscx = 1 secx-cosx/secs=sin^2x
    1. answers icon 1 answer
  4. Simplify #1:cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer
    1. answers icon 1 answer
more similar questions